PENGALIHAN JABATAN STRUKTURAL KE FUNGSIONAL PADA DINAS PEMADAM KEBAKARAN KOTA MEDAN - Elika, Cut; Sinaga, Rudi Salam; Lubis, Khairunnisa (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to describe the transfer of structural positions to functional positions in the Medan City Fire Department and identify the factors that hinder the implementation of this transfer. The transfer of structural positions to functional positions is an administrative requirement determined for each position, so that job duties can be carried out properly, and environmental fire safety management must be supported by personnel with expertise in fire management. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results show that the transfer of structural positions to functional positions in the Medan City Fire Department still has employees whose educational background does not match their position. Other obstacles include changes in responsibility and employee tasks. The transfer of positions often requires adjustments in roles, authority, and responsibility, which can cause confusion or uncertainty among employees. To overcome these obstacles, it is recommended that there be preparation in carrying out the transfer of structural positions to functional positions so that the transfer process does not experience obstacles. The Medan City Fire Department should also increase employee motivation to improve performance, such as by providing rewards and recognition.